Theoretical study of Solospun yarn torque. Issue 5 (7th September 2015) - Liu, Xinjin; Su, Xuzhong
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Solospun technology is one of the most important new spinning methods, which is implemented by dividing Ring spinning triangle into several small primary triangles and one final triangle by a Solospun roller. That is, there are two parts of spinning triangle in the Solospun technology, including primary triangles part and final triangle part. In the general case, the primary triangles are much smaller than final triangle. Therefore, the purpose of this paper is to present theoretical study of Solospun yarn torqueby linking the fiber tension in the spinning triangle to yarn torque under the assumption that the primary triangles and the primary twist are ignored. Design/methodology/approach – The theoretical model of the residual torque within Solospun yarn due to the fiber tension was given. Then, as an application of the proposed method, 14.6 tex cotton yarns were taken as an example for the numerical simulations. The fiber tension in the Solospun spinning triangles and corresponding yarn torque were simulated numerically by using Matlab software. The relationships between yarn torque and spinning triangle parameters are analyzed according to the simulation results. Furthermore, the properties of spun yarns produced by the Solospun and Ring spinning system are evaluated and analyzed by using the simulation results. Findings – It is shown that comparing with the Ring spun yarn, Solospun yarn torque is a little larger. Meanwhile, with an increase of substrand number, the fluctuation of curve of average fiber tension in Solospun system is increased firstly, and then decreased, i.e. showing parabola shape, potentially leading to corresponding change of yarn torque. Originality/value – In this paper, theoretical study of Solospun yarn torque is presented by linking the fiber tension in the spinning triangle to yarn torque under the assumption that the primary triangles and the primary twist are ignored. The theoretical model of the residual torque within Solospun yarn due to the fiber tension was given.